(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background:Undescended testis is one of the most common malformations seen in the field of pediatric surgery. The most problematic aspect of undescended testis is the diagnosis and treatment of nonpalpable testis. Laparoscopy has been widely used for the diagnosis and treatment of nonpalpable testis. Objective:To evaluate the role of laparoscopy in the diagnosis and treatment of unilateral nonpalpable undescended testis. Methods:This is a prospective study carried out in the period from December 2012 to December 2017 in the Pediatric Surgery Department of a tertiary hospital in Baghdad. We used laparoscopy in the diagnosis and treatment of 40 patients aged between one and 12 years (median age 4.9 years) with unilateral nonpalpable undescended testis. Boys with a palpable testis at any point were excluded from the study. Surgical procedure was individualized according to the laparoscopic findings either by one stage laparoscopic orchiopexy, two stage Fowler-Stephens procedure or laparoscopic orchiectomy. Results:Laparoscopy was able to diagnose the site of the nonpalpable testes in all the patients. Out of 40 nonpalpable undescended testes, 26 testes (65%) were intra-abdominal (12 testes were low intra-abdominal, 14 testes were high intra-abdominal). In 9 patients, (22.5 %), the vas deferens and spermatic vessels were found entering the internal inguinal ring. In 3 patients, (7.5 %), the testes were vanishing, and the testes were absent in 2 patients (5%). All patients with low intra-abdominal testes (n=12) were subjected to one stage laparoscopic orchiopexy through the normal inguinal ring. Out of 14 patients with high intra-abdominal testes, 7 patients underwent two staged Fowler-Stephens laparoscopic procedures, while three patients were treated by laparoscopic Prentiss maneuver and the remaining 4 patients underwent immediate laparoscopic orchiectomy due to presence of an atrophied testis. Patients with the vas deferens and spermatic vessels entering the internal inguinal ring (n=9) were treated by orchiopexy via conventional inguinal approach. Conclusion:Laparoscopy for unilateral nonpalpable testis has an excellent diagnostic yield combined with high success rate following repair. Keywords:Laparoscopy, nonpalpable undescended testis, Fowler-Stephens procedure Citation:Zain AZ, Mohammed NH, Fadil SZ, Abdul-Hassan BA. Efficacy of laparoscopy in the management of unilateral nonpalpable testis. Iraqi JMS. 2019; 17(3&4): 223-230. doi: 10.22578/IJMS.17.3&4.9